The effectiveness of the combination of 5-finger hypnosis and deep breathing relaxation techniques to reduce anxiety in adolescent students - Sarini Sarini; Desty Lismayanti; Yanti Rosmiyanti; Sumitro Sumitro; Okti Rahayu Asih; Dewi Rubi Fitriani; Jumaedi Jumaedi (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Students of grade XII of vocational high school will take the final competency test of vocational skills in February-March 2026. They are required to pass the competency test so that this causes anxiety and tension in students of grade XII of vocational high school. Actions to overcome anxiety in students of grade XII of vocational high school can be done with pharmacological and non-pharmacological therapy. 5-finger hypnosis and a combination of deep breathing relaxation are non-pharmacological therapies that can reduce anxiety in students of grade XII of vocational high school. 5-finger hypnosis combined with deep breathing relaxation therapy will provide a calming effect on anxiety and tension experienced by students. Purpose: To determine the effect of 5-finger hypnosis and a combination of deep breathing relaxation on anxiety levels in students. Method: This type of research uses a pretest and post-test design. This study used a sample of 60 students of grade XII of SMK Sehati Karawang with 30 students given a combination of deep breathing and 5-finger hypnosis intervention and 30 students as control variables. Results: The results of the study showed a significant difference in anxiety levels before and after being given a combination of deep breathing relaxation and 5-finger hypnosis in students who were given the intervention. Conclusion: One effective non-pharmacological intervention for reducing adolescent anxiety is a combination of deep breathing relaxation and five-finger hypnosis. This therapy helps individuals achieve a relaxed state by imagining positive experiences, thereby reducing physical and psychological tension.